Proceedings of the Second ACM Conference on Online Social Networks 2014
DOI: 10.1145/2660460.2660481
|View full text |Cite
|
Sign up to set email alerts
|

WTF, GPU! computing twitter's who-to-follow on the GPU

Abstract: In this paper, we investigate the potential of GPUs for performing link structure analysis of social graphs. Specifically, we implement Twitter's WTF ("Who to Follow") recommendation system on a single GPU. Our implementation shows promising results on moderate-sized social graphs. It can return the top-K relevant users for a single user in 172 ms when running on a subset of the 2009 Twitter follow graph with 16 million users and 85 million social relations. For our largest dataset, which contains 75% of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…The state-of-the-art CUDA implementation of BFS [10] uses best-effort synchronization approaches, that avoid the use of atomic operations but provide a degree of filtering of duplicated elements. SSSP [16] and PR [4] use atomic operations to avoid duplication, yet incur in significant overheads. Taking BFS as an example, its exploration consists of two main phases or kernels: Expansion and Contraction.…”
Section: Gpgpu Graph Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The state-of-the-art CUDA implementation of BFS [10] uses best-effort synchronization approaches, that avoid the use of atomic operations but provide a degree of filtering of duplicated elements. SSSP [16] and PR [4] use atomic operations to avoid duplication, yet incur in significant overheads. Taking BFS as an example, its exploration consists of two main phases or kernels: Expansion and Contraction.…”
Section: Gpgpu Graph Processingmentioning
confidence: 99%
“…G RAPH-BASED applications are ubiquitous in important domains such as data analytics [1] or machine learning [2] among many other examples. Road navigation and self-driving cars [3], recommendation systems [4] and speech recognition [5] are paradigmatic examples of graph processing workloads. Current trends towards increased data gathering [6] and knowledge-based applications result in an increased importance of graph-based applications and, at the same time, a demand for higher data processing capabilities, which motivates high-throughput graph processing on GPGPU architectures.…”
Section: Introductionmentioning
confidence: 99%
“…In Gunrock, we begin with a frontier that contains all vertices in the graph and end when all vertices have converged. Each iteration contains one advance operator to compute the PageRank value on the frontier of vertices, and one filter operator to remove the Bipartite graphs Geil et al [9] used Gunrock to implement Twitter's who-to-follow algorithm ("Money" [11]), which incorporated three node-ranking algorithms based on bipartite graphs (Personalized PageRank, Stochastic Approach for Link-Structure Analysis (SALSA), and Hyperlink-Induced Topic Search (HITS)). Their implementation, the first to use a programmable framework for bipartite graphs, demonstrated that Gunrock's advance operator is flexible enough to encompass all three node-ranking algorithms, including a 2-hop traversal in a bipartite graph.…”
Section: Pagerank and Other Node Ranking Algorithmsmentioning
confidence: 99%
“…Bipartite graphs Geil et al [9] used Gunrock to implement Twitter's who-to-follow algorithm ("Money" [11]), which incorporated three node-ranking algorithms based on bipartite graphs (Personalized PageRank, Stochastic Approach for Link-Structure Analysis (SALSA), and Hyperlink-Induced Topic Search (HITS)). Their implementation, the first to use a programmable framework for bipartite graphs, demonstrated that Gunrock's advance operator is flexible enough to encompass all three node-ranking algorithms, including a 2-hop traversal in a bipartite graph.…”
Section: Pagerank and Other Node Ranking Algorithmsmentioning
confidence: 99%